Effectiveness of a laboratory-scale vertical tower static chamber steam pasterurization unit against Escherichia coli 0157:H7, salmonella typhimurium, and listera innocua on prerigor beef tissue - Retzlaff, Deanna D.; Phebus, Randall K.; Nutsch, Abbey L.; Riemann, James; Kastner, Curtis L.; Marsden, James L. (My University, 2008)
A laboratory-scale vertical tower steam pasteurization unit was evaluated to determine the antimicrobial effectiveness of different exposure times (0, 3, 6, 12, and 15 s) and steam chamber temperatures (82.2, 87.8, 93.3, and 98.9°C) against pathogens (Escherichia coli O157:H7, Salmonella Typhimurium, and Listeria innocua) inoculated onto prerigor beef tissue. Samples were collected and microbiologically analyzed immediately before and after steam treatment to quantify the effectiveness of each time-temperature combination. The 0-s exposure at all chamber temperatures (cold water spray only, no steam treatment) was the experimental control and provided 0.3 log CFU/cm2 reductions. Chamber temperatures of 82.2 and 87.8°C were ineffective (P > 0.05) at all exposure times. At 93.3°C, significant reductions (> 1.0 log CFU/cm2) were observed at exposure times of 6 s, with 15 s providing approximately 1 log cycle greater reductions than 12 s of exposure. The 98.9°C treatment was consistently the most effective, with exposure times of 9 s resulting in >3.5 log CFU/cm2 reductions for all pathogens.
Keywords: Beef; Pasteurization; Decontamination; Steam; E. coli; Salmonella